Spatiotemporal Coherence of Low Water Levels and Mechanism of Transfer from Meteorological to Hydrological and Agricultural Droughts - Bossa, Yaovi Aymar; Amoussou, Ernest; ASSANI, Afoussath; Djangni, Octave; Hounkpè, Jean; PATUREL, Jean-Emmanuel (My University, 2023)
Drought is a serious environmental disaster that affects many parts of the world. It is defined as a prolonged absence or marked deficiency of rainfall. It can be detected by various drought indices (meteorological, hydrological, and agricultural). This water deficit is accentuated by the drought that has persisted in the study area since the mid-1970s. Moreover, the absence of study on the characterization of drought in the Ouémé River Basin invites, through this research work, to study drought at the level of the Ouémé River Basin in Bonou and its impact on water resources. The data used covers a period of 30 years (1989-2020). Thus, for the characterization of drought, three indices (SPI, SDI, and Martonne aridity index) were determined. These indices were used to make a spatiotemporal analysis of the drought in the basin through some hydrometric stations. From the analysis of the results, the drought states vary from one year to another with a preponderance of the Light drought state even if in the most recent years, an evolution to a moderate or even extreme drought state has been observed. The drought conditions vary from one area to another due to the different rainfall, the nature of the soil and the human activities in each area. In addition, there is a higher probability of transition from meteorological to hydrological drought in the Ouémé River Basin.
Keywords: Hydrological drought; Drought index; Ouémé River Basin